Strategies to Help Students Solve Addition and Subtraction Word Problems. (April 2022) - Peltier, Corey; VanDerHeyden, Amanda M.; Hott, Brittany L.
Successful math word-problem solving is difficult for some students. Getting the right answer involves students engaging correctly in an amalgamation of actions. Schema instruction is an instructional approach aimed at supporting students in identifying the underlying math problem structure to yield an appropriate solution plan. The focus of this article is on supporting educators in understanding the core ingredients of schema instruction and explaining how to implement it effectively with students with elementary grades emotional and behavioral disorders.